Por trás dos muros escolares: luzes e sombras na educação feminina (Colégio N. Sra. das Dores - Uberaba 1940/1966) - Moura, Geovana Ferreira Melo (2002)
This work has as study object the history of the feminine education in Colégio Senhora das Dores of Uberaba, in the years 1940 to 1966, focalizing the school institution as a space of students' formation. It is a reflection on the Catholic confessional teaching, offered by Dominican Sisters. The study evidences perspectives of analyses about the school institutions, demonstrating the directions of the current historiography that it has been valuing the private subjects, that is to say, that attributes value to the local and regional specify. We also revisited the history of Uberaba, the first school institutions of the area and the arrival of the Dominican Sisters in Brazil, in 1885. The analysis of the primary sources of the School - record books, reports, documents, letters and annotations - besides the techniques of the Oral History, through the people's deposition involved in the scenery of the School students and teachers were understood as important methodological resources. Starting from the accomplished interpretations, we had the understanding that the families transferred to the School the function of educating and to form their daughters, in agreement with the desirable woman patterns for the patriarchal society at that time. The girl would then, be learned, apprentice of the Catholic religion, gifted and prepared to the " sweetness " of home and maternity.